Deficiency of Intellectual Disability-Related Gene Brpf1 Attenuated Hippocampal Excitatory Synaptic Transmission and Impaired Spatial Learning and Memory Ability - Xian, Weiwei; Cao, Jingli; Yuan, Xiangshan; Wang, Guoxiang; Jin, Qiuyan; Zhang, Hang; Zhou, Guomin; You, Linya (Frontiers in Cell and Developmental Biology, 2021)
Patients with monoallelic bromodomain and PHD finger-containing protein 1 (BRPF1) mutations showed intellectual disability. The hippocampus has essential roles in learning and memory. Our previous work indicated that Brpf1 was specifically and strongly expressed in the hippocampus from perinatal period to adulthood. We hypothesized that mouse Brpf1 plays critical roles in the morphology and function of hippocampal neurons, and its deficiency leads to learning and memory deficits. To test this, we performed immunofluorescence, whole-cell patch clamp, mRNA-Seq on shBrpf1 infected primary cultured hippocampal neurons to study the effect of Brpf1 knockdown on neuronal morphology, electrophysiological characteristics and gene regulation. In addition, we performed stereotactic injection into adult mouse hippocampus to knockdown Brpf1 in vivo and examined the learning and memory ability by Morris Water Maze. We found that mild knockdown of Brpf1 reduced mEPSC frequency of cultured hippocampal neurons, before any significant changes of dendritic morphology showed. We also found that Brpf1 mild knockdown in the hippocampus showed a decreasing trend on the spatial learning and memory ability of mice. Finally, mRNA-Seq analyses showed that genes related to learning, memory and synaptic transmission (such as C1ql1, Gpr17, Htr1d, Glra1, Cxcl10 and Grin2a) were dysregulated upon Brpf1 knockdown. Our results showed that Brpf1 mild knockdown attenuated hippocampal excitatory synaptic transmission and reduced spatial learning and memory ability, which helps explain the symptoms of patients with BRPF1 mutations.